The molecular targets of diclofenac differs from ibuprofen to induce apoptosis and epithelial mesenchymal transition due to alternation on oxidative stress management p53 independently in PC3 prostate cancer cells - AKAR, REMZİ OKAN; Çoker Gürkan, Ajda; Akın, Beyza; Dener, Elif; Kayhan, Ecem; Palavan Ünsal, Narçın; YERLİKAYA, PINAR OBAKAN; ARISAN, ELİF DAMLA; RENCÜZOĞULLARI, ÖZGE (Elsevier INC., 2019)
Background: Prostate cancer is the most common type of cancer among men. Studies showed that the regular use of nonsteroidal antiinflammatory drugs might reduce disease progression risk for prostate cancer patients with prostate cancer. We evaluated the effects of ectopic expression of p53 on the biological functions of ibuprofen and diclofenac. Materials and methods: For this purpose, We investigated cell death decision pathways related to survival and aggressive cellular phenotypes such as extrinsic/intrinsic apoptosis decision, Protein Kinase B/ Forkhead box O (AKT/FoxO) axis, mitogen-activated protein kinases (MAPKs), reactive oxygen species (ROS) generation, and EMT (epithelial mesenchymal transition) in wild type and p53 + PC3 prostate cancer cells. Results and Conclusions: Ibuprofen (1 mM) and diclofenac (250 mu M) effectively induced cell cycle arrest and led to apoptosis via modulating both extrinsic and intrinsic pathways. However, diclofenac was the only drug to generate ROS intermediates. Diclofenac triggered a typical EMT process with downregulated E-cadherin and upregulated N-cadherin, vimentin, and Snail in PC3 cells, regardless of p53 expression. In conclusion, although both drugs are effective on cell death mechanism, only diclofenac caused EMT because of increased ROS generation independent of p53. On the other hand, ibuprofen could inhibit metastasis via upregulating E-cadherin. The biological targets of both nonsteroidal antiinflammatory drugs are different to highlight their role in cell survival and death axis. (c) 2019 Asian Pacific Prostate Society, Published by Elsevier Korea LLC. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Apoptosis; Diclofenac; Epithelial Mesenchymal Transition; Ibuprofen; Nonsteroidal Antiinflammatory Drugs; Prostate Cancer; Reactive Oxygen Species